2013
DOI: 10.1603/me12165
|View full text |Cite
|
Sign up to set email alerts
|

Myiasis by <I>Megaselia scalaris</I> (Diptera: Phoridae) in a Python Affected by Pulmonitis

Abstract: Myiases are caused by the presence of maggots in vertebrate tissues and organs. Myiases have been studied widely in humans, farm animals, and pets, whereas reports of myiasis in reptiles are scarce. We describe a case of myiasis caused by the Megaselia scalaris (Loew) in an Indian python (Python molurus bivittatus, Kuhl) (Ophida: Boidae). The python, 15 yr old, born and reared in a terrarium in the mainland of Venice (Italy), was affected by diffuse, purulent pneumonia caused by Burkholderia cepacia. The sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
(15 reference statements)
1
2
0
1
Order By: Relevance
“…As our previous study found, B. cepacia has an involvement to the respiratory tract in reptiles (Purbantoro et al, 2018). Similar result of B. cepacia finding and similar clinical signs were also reported by the studies of, Santos et al (2008) and Vanin et al (2013). API system 20 NE was performed in one more case with positive results of Burkholderia cepacia (Ebani et al, 2008).…”
Section: Results In Tablesupporting
confidence: 87%
See 1 more Smart Citation
“…As our previous study found, B. cepacia has an involvement to the respiratory tract in reptiles (Purbantoro et al, 2018). Similar result of B. cepacia finding and similar clinical signs were also reported by the studies of, Santos et al (2008) and Vanin et al (2013). API system 20 NE was performed in one more case with positive results of Burkholderia cepacia (Ebani et al, 2008).…”
Section: Results In Tablesupporting
confidence: 87%
“…Compromised immune system occurs with chronic illness, poor nutrition, or other factors (improper husbandry) (Hilf et al, 1990;Schumacher, 2003). The pathogens mainly occur in individuals with compromised immune state (Ebani and Fratini, 2005;Vanin et al, 2013).…”
Section: Results In Tablementioning
confidence: 99%
“…Therefore, they have been used in forensic science to estimate postmortem intervals particularly in tightly enclosed containments (Disney, 2008; Reibe and Madea, 2010). They are also facultative parasites causing Myiasis (infestation of living tissue with maggots) in animals including humans (Disney, 2008; Hira et al, 2004; Ghavami and Djalilvand, 2015; Vanin et al, 2013). Recent advancements in genomic studies and the convenience of maintaining colonies in the laboratory make this and related species ( M. abdita ) as an emerging model system in evolutionary biology (Rafiqi et al, 2011; Wotton et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Por su parte, el grupo de moscas fóridas (principalmente el género Megaselia) provocan miasis en diversos reptiles a nivel mundial (Silva et al, 1999;Vanin et al, 2013) y parasitan nidos de otras especies (Holcomb y Carr, 2011), con registros incluso en Colombia en nidos de Iguana iguana (Muñoz et al, 2003) e hicotea (Restrepo et al, 2007). Aunque hasta el momento no se han encontrado otros reportes de esta familia de dípteros en nidos del género Podocnemis, su amplia distribución y su gran diversidad (Brown, 2010;Ament y Brown, 2016) les da un potencial importante como depredadores, por lo que es muy probablemente que a medida que se incrementen los estudios, emerjan más ejemplos.…”
Section: Resultados Y Discusiónunclassified